ARbis Pictus: A Study of Vocabulary Learning with Augmented Reality - Ibrahim, Adam; Huynh, Brandon; Downey, Jonathan; Hollerer, Tobias; Chun, Dorothy; O'donovan, John (IEEE transactions on visualization and computer graphics, 2018)
We conducted a fundamental user study to assess potential benefits of AR technology for immersive vocabulary learning. With the idea that AR systems will soon be able to label real-world objects in any language in real time, our within-subjects (N=52) lab-based study explores the effect of such an AR vocabulary prompter on participants learning nouns in an unfamiliar foreign language, compared to a traditional flashcard-based learning approach. Our results show that the immersive AR experience of learning with virtual labels on real-world objects is both more effective and more enjoyable for the majority of participants, compared to flashcards. Specifically, when participants learned through augmented reality, they scored significantly better on both same-day and 4-day delayed productive recall tests than when they learned using the flashcard method. We believe this result is an indication of the strong potential for language learning in augmented reality, particularly because of the improvement shown in sustained recall compared to the traditional approach.